Virtual teambuilding and ICT technologies in relation involving the theories of social presence and media richness [Virtuelles Teambuilding und IKT-Technologien in Relation unter Einbeziehung der Theorien Social Presence und Media Richness] - (:unkn) unknown (My University, 2012)
[No abstract available]